Re-conceptualizing Museum Audiences: Power, Activity, Responsibility - Stylianou-Lambert, Theopisti (My University, 2010)
This article offers a theoretical overview of how diverse disciplines, such as cultural studies, sociology, philosophy of art, education, and marketing, have contributed to the evolving conceptualization of museum audiences over the past 50 years. Audience research has moved through different paradigms. Every shift in the way audiences are viewed unavoidably influences the way museum professionals view themselves, their role, and the way they interact with their audiences. The most recent audience conceptualization envisions visitors as active interpreters who selectively construct meaning based on their personal experiences, associations, biases, and sense of identity, while the museum is envisioned as an open work that is only completed by the visitor. However, certain challenges loom over this new audience conceptualization. It is argued that such visualization underestimates power issues while romanticizing the power of audience activity, thereby ignoring issues of responsibility.
Keywords: Museum; Museums; Job ads